2019
DOI: 10.1111/anae.14866
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for safe transfer of the brain‐injured patient: trauma and stroke, 2019

Abstract: Summary The location of care for many brain‐injured patients has changed since 2012 following the development of major trauma centres. Advances in management of ischaemic stroke have led to the urgent transfer of many more patients. The basis of care has remained largely unchanged, however, with emphasis on maintaining adequate cerebral perfusion as the key to preventing secondary injury. Organisational aspects and training for transfers are highlighted, and we have included an expanded section on paediatric t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 21 publications
0
14
1
1
Order By: Relevance
“…In this study, the mean hospital arrival ETCO 2 was 4.1 (±0.7) kPa (30.7 mm Hg), which suggests that the prehospital providers adhered closely to the extant guidelines. Despite this, the mean PaCO 2 was 5.8 (±1.1) kPa (43.3 mm Hg)—far in excess of the target of 4.5–5.0 kPa, 24 owing to a mean ETCO 2 –PaCO 2 gradient of 1.7 (±1.0) kPa (12.8 mm Hg). The result of this is that when relying on ETCO 2 as a surrogate, providers may not achieve an optimal prehospital PaCO 2 .…”
Section: Discussionmentioning
confidence: 90%
“…In this study, the mean hospital arrival ETCO 2 was 4.1 (±0.7) kPa (30.7 mm Hg), which suggests that the prehospital providers adhered closely to the extant guidelines. Despite this, the mean PaCO 2 was 5.8 (±1.1) kPa (43.3 mm Hg)—far in excess of the target of 4.5–5.0 kPa, 24 owing to a mean ETCO 2 –PaCO 2 gradient of 1.7 (±1.0) kPa (12.8 mm Hg). The result of this is that when relying on ETCO 2 as a surrogate, providers may not achieve an optimal prehospital PaCO 2 .…”
Section: Discussionmentioning
confidence: 90%
“…Several organisations have produced guidelines for the management of TBI [7–9]. Key elements of the most commonly used are summarised in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, more patients with TBI have comorbid medical conditions which are associated with an increase in all-cause mortality rates [6]. Several organisations have produced guidelines for the management of TBI [7][8][9]. Key elements of the most commonly used are summarised in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…While some had recognised this should change [4], and national guidelines and safety reports had recommended improvements [5][6][7], funding and resources were lacking. This landscape was the situation within which Huq et al [8] found themselves at the beginning of the COVID-19 pandemic.…”
mentioning
confidence: 99%
“…Before the COVID‐19 pandemic, dedicated services were operational, or in development, in the devolved nations of Northern Ireland, Scotland and Wales, but no provision had been made in England outside extracorporeal membrane oxygenation retrieval services. While some had recognised this should change [ 4 ], and national guidelines and safety reports had recommended improvements [ 5 , 6 , 7 ], funding and resources were lacking. This landscape was the situation within which Huq et al.…”
mentioning
confidence: 99%